Islamic reform in South Asia - Osella, Filippo; Osella, Caroline (Cambridge ; New York : Cambridge University Press, 2013)
"Discusses contemporary Islamic reformism in South Asia in some of its diverse historical orientations and geographical expressions"--Provided by publisher.
Reformist journeys -- Debating reform -- Everyday politics of reform -- Reform, state and market.
Includes bibliographical references and index.
Print version record.
Keywords: Islam -- South Asia -- History; Islamic renewal -- South Asia; RELIGION / Islam / General; Electronic books